TPCK of Mathematics Trainee Teachers: A Comparison using Mahalanobis Distance - Subir Sen; Birbal Saha (Scientia Publica Media, 2026)
This body of knowledge, known as ‘Technological Pedagogical Content Knowledge (TPCK)’, is essential to teaching both today and in the future. Teachers possess a high degree of knowledge that is based on ‘Pedagogical Knowledge (PK)’, ‘Technological Knowledge (TK)’, ‘Content Knowledge (CK)’, ‘Technological Pedagogical Knowledge (TPK)’, ‘Technological Content Knowledge (TCK)’, and ‘Pedagogical Content Knowledge (PCK)’. This research work was done by collecting data from B.Ed. trainee teachers with mathematics as a method subject in West Bengal, India. The objective of the study is to compare the TPCK knowledge base of mathematics trainee teachers with respect to gender and residence. The descriptive Survey Method is followed. Trainee teachers with mathematics as a method subject from West Bengal, India, are taken as a sample. The TPACK-Math Scale by Önal (2016) is used for this study. Collected data is prepared by using MS Excel, analysed by SPSS 26, JASP 0.18.1, and MATLAB 2021b. Descriptive statistics (Mean, SD, and Covariance) and inferential statistics (Mahalanobis Distance) are used for this study. Calculated value of Mahalanobis Distance between male and female is 0.3417 (<1) and between rural and urban is 0.6625 (<1). There is no significant difference between male vs female and rural vs urban mathematics trainee teachers with respect to ‘TK’, ‘PK’, ‘CK’, ‘TPK’, ‘TCK’, ‘PCK’, ‘CNTK’, and ‘TPCK’. It is concluded that the dynamical nature of the knowledge base considered for the present study is independent of gender and residence of trainee teachers. Possible causes for such a non-significant finding in the educational research context are discussed. A comprehensive interpretation of the inherent limitations is acknowledged, and to overcome these limitations and deepen the understanding of TPCK development in mathematics education, further research is suggested.